2018
DOI: 10.1016/j.ijom.2017.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuating asymmetry of the normal facial skeleton

Abstract: The purpose of this study was to produce reliable estimations of fluctuating facial asymmetry in a normal population. Fifty-four computed tomography (CT) facial models of average-looking and symmetrical Chinese subjects with a class I occlusion were used in this study. Eleven midline landmarks and 12 pairs of bilateral landmarks were digitized. The repeatability of the landmark digitization was first evaluated. A Procrustes analysis was then used to measure the fluctuating asymmetry of each CT model, after all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 27 publications
1
8
1
Order By: Relevance
“…First, that body and face size are allometrically related in adults and that facial FA is a by‐product of individual growth. In contrast to previous studies (e.g., Gateño et al, 2018; Mitteroecker et al, 2013), the results were compatible, with high uncertainty, with an effect close to zero. These results suggest that more discussion is needed on the empirical causal model derived for this hypothesis.…”
Section: Discussioncontrasting
confidence: 99%
“…First, that body and face size are allometrically related in adults and that facial FA is a by‐product of individual growth. In contrast to previous studies (e.g., Gateño et al, 2018; Mitteroecker et al, 2013), the results were compatible, with high uncertainty, with an effect close to zero. These results suggest that more discussion is needed on the empirical causal model derived for this hypothesis.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, we exhibited that even the included normal individuals presented with a certain degree of facial asymmetry as revealed by both the 2D and 3D photogrammetric methods. As this finding has widely been demonstrated for normal populations 34,46 , valid deductions could be made from normal-related comparisons. Different from mid-face or nasolabial measurement-based outcome investigations 35,36,47 , in this study we addressed particularly the lower face region.…”
Section: Lateral Lower Chin N (%)supporting
confidence: 55%
“…[19][20][21][22] However, these studies reported the symmetry of volume and measurement values such as the angle only on unilateral sides, and the reference plane of the symmetry was different in each study. 23,24 Furthermore, threedimensional anatomical and locational symmetry between both sides of the orbits has not been studied. These are crucial factors, especially in the orbital area, because they are directly related to the accuracy of the mirroring technology and surgical outcomes.…”
Section: Discussionmentioning
confidence: 99%